Analysis of Reversed L-loops as Closing Loops with Anterior Intrusive Force. (September 2018) - Techalertpaisarn, Paiboon; Versluis, Antheunis
Objective: Intrusive forces on anterior brackets are preferable for avoiding overbite deepening. Reversing plain L-loops may create such advantageous force system during space closure. Design: Force systems of reversed L-loops were compared with T-loops at three interbracket distances (IBD). Setting: Computational study. Methods: Using finite element analysis, loop response during simulated loop-pulling was determined for plain reversed L- and T-loop configurations at three IBDs and two sizes. Force systems were calculated on both loop ends for two activation forces. Results: The 12 mm IBD reversed L-loops had almost equal M/F ratios in opposite directions at both ends. A small intrusive force was found at the canine bracket (CB). The 6 mm IBD reversed L-loops showed larger M/F ratios and extrusive forces at the premolar bracket (PB) and smaller M/F with intrusive forces at CB. The force system of 12 mm IBD T-loops showed the similar force systems as off-centered V-bends with extrusive force at CB, whilst plain 6 mm IBD T-loops showed properties similar to centered V-bends with less extrusive force at CB. Conclusions: Reversed L closing loops placed no extrusive force on the CB end at various IBDs, indicating that reversed loops will generate an intrusive force at anterior teeth during space closure.